دراسة استقرار كمي للنقاط السرجية المشروطة (Latakia University Journal -Basic Sciences Series, 2018)
الهدف من هذا البحث هو دراسة مترية للنقاط السرجية المشروطة لدوال محدبة –مقعرة ودوال ليست بالضرورة  محدبة- مقعرة دون استخدام شروط الأمثلية, وتعميم بعض النتائج المتعلقة بالنقاط الأصغرية المحلية لدوال محدبة وغير محدبة مستخدمين مفهوم مسافة هاوسدورف فوق البيانية . The objective of this research is a metric study of conditional saddle points of convex - concave functions, not necessarily convex - concave without the use of optimization conditions. Dissemination of some of the results related to the minimizer local points for the functions are not necessarily convex using  to the concept of epigraphical  distance  of Hausdorff .